2004
DOI: 10.1074/jbc.m309158200
|View full text |Cite
|
Sign up to set email alerts
|

Estradiol Binding to Maxi-K Channels Induces Their Down-regulation via Proteasomal Degradation

Abstract: Estrogens exert their biological action via both genomic and non-genomic mechanisms. Proteins different from classical estradiol receptors are believed to mediate the latter effects. Here we demonstrate that the maxi-K channel functions as an estrogen-binding protein in transfected HEK293 cells. Whole-cell maxi-K channel currents and protein expression were attenuated by exposure to either 17␣-or 17␤-estradiol. This effect was dose-dependent for 17␤-estradiol at concentrations ranging from 10 nM to 1 M, while … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(22 citation statements)
references
References 33 publications
2
20
0
Order By: Relevance
“…1B); the results were similar to previous reports (25,26). However, when we coexpressed the two channels, BK current amplitude fell ( Fig.…”
Section: Asic1asupporting
confidence: 82%
See 1 more Smart Citation
“…1B); the results were similar to previous reports (25,26). However, when we coexpressed the two channels, BK current amplitude fell ( Fig.…”
Section: Asic1asupporting
confidence: 82%
“…cDNA constructs were either previously reported or were generated by using standard procedures. HEK293 cells stably expressing BK were previously reported (25).…”
Section: Methodsmentioning
confidence: 99%
“…Strong evidence now supports the idea that steroids can bind to cell surface proteins to trigger downstream signaling cascades in the cell (44). Rapid effects of estrogen and aldosterone via plasma membrane transport mechanisms, such as Ca 2ϩ -and voltage-activated K ϩ channels and the Na ϩ /H ϩ exchanger, have been reported (45,46). The effect of ouabain in ADPKD cells is consistent with that observed in several other cell types, in which ouabain binding to the Na,K-ATPase triggers ERK phosphorylation (15).…”
Section: Discussionmentioning
confidence: 85%
“…Indeed, non-genomic effects of E 2 on maxi-K current have been demonstrated by its ability to induce channel openings when the channel a subunit is associated with either the accessory b1 or the b4 subunit, but not in their absence [14,18,19]. More recently, using HEK-293 cells transfected with maxi-K channels, Korovkina et al [20] demonstrated that estrogens bind to maxi-K channels and may directly regulate channel function. Estrogens are also known to regulate maxi-K channel activity by several cellular signalling mechanisms: (i) the activation of nitric oxide synthase (NOS) in uterine cells [21]; (ii) the cGMP-dependent phosphorylation in coronary arteries [4,15].…”
Section: Discussionmentioning
confidence: 99%